2016
DOI: 10.1111/myc.12474
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis in Iran: a systematic review

Abstract: Fungi in the order Mucorales cause acute, invasive and frequently fatal infections in susceptible patients. This study aimed to perform a systematic review of all reported mucormycosis cases during the last 25 years in Iran. After a comprehensive literature search, we identified 98 cases in Iran from 1990-2015. The mean patient age was 39.8 ± 19.2 years. Diabetes was the most common underlying condition (47.9%), and 22.4% of the patients underwent solid organ or bone marrow transplantation. The most common cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
80
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 68 publications
20
80
2
5
Order By: Relevance
“…Risk factors of mucormycosis infection include diabetes, acidosis, malignancy, organ transplantation, granulocyte deficiency, glucocorticoid use, AIDS, trauma, malnutrition, and usage of deferoxamine [6,[12][13][14]. Mucormycosis infection could also be found in patients with normal immune function, especially those with trauma or skin damage [15].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors of mucormycosis infection include diabetes, acidosis, malignancy, organ transplantation, granulocyte deficiency, glucocorticoid use, AIDS, trauma, malnutrition, and usage of deferoxamine [6,[12][13][14]. Mucormycosis infection could also be found in patients with normal immune function, especially those with trauma or skin damage [15].…”
Section: Discussionmentioning
confidence: 99%
“…The most common form is the rhinocerebral one [3,[8][9][10] and it is found in 44-49% of all detected zygomycosis. Retrospective analysis of 98 cases made by Vaezi et al [11] showed that rhinocerebral form, characterized by the highest mortality rate was detected most frequently in the gathered data (about 48.9% of all clinical subtypes of rhinocerebral zygomycosis). For comparison: the sinonasal -7.1% and sinonasaloorbital -6.1% forms were not often found.…”
Section: Incidence and Prevalencementioning
confidence: 96%
“…At least 25% is a group with severe trauma [13]. Vaezi et al [11] also indicates that diabetes is the most common predisposing factor (47.9%), while the second one are organ or bone marrow diseases -22.4%. Different statistics were presented by ECMM study group.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…These infections can be quite devastating, causing complications such as tissue necrosis and necrotizing fasciitis, especially in immunocompromised individuals (Neblett Fanfair et al , 2012). There is substantial morbidity and mortality associated with these infections (Vaezi et al , 2016). …”
Section: Introductionmentioning
confidence: 99%